A study of Samuel Beckett's plays in English with special reference to their development through drafts and to structural patterning - Pountney, R; Pountney, Rosemary (1978)
﻿ This thesis is a study of Beckett's later plays (those written in English as a first language) beginning with All That Fall. There are three main areas of investigation. Part One considers the importance of structure in Beckett's writing and the extreme precision with which his plays are patterned. The circular movement found in most of the plays is seen to reflect Beckett's constant theme of the human life cycle, in a precise fusion of content with form. Part Two, the bulk of the study, considers the evolution of the plays through their various drafts. The exploration of a large body of draft material affords some insight into Beckett's characteristic approach to his writing, his working method and the craftsmanship with which the plays are shaped, both structurally and linguistically. A tendency for ambiguity to develop and increase as the drafts progress is discovered in the plays. Part Three considers the plays in performance and discusses the various aspects of Beckett's dramatic technique in the writing, acting and direction of the plays. The innovatory quality of Beckett's dramatic ideas is observed in his work for the different media of stage, radio, cinema and television. The discussion thus seeks to increase our understanding of Beckett's plays in English by studying not only the structures ultimately arrived at, but the process of gestation also and finally by observing their efficacy in production.